2020
DOI: 10.1002/lary.29175
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Impact of Hearing Aid Provision or Cochlear Implantation on Hearing Handicap

Abstract: Objectives/Hypothesis Previous research has shown hearing handicap to be reduced following hearing aid use or cochlear implantation in short‐to‐medium follow‐up periods, yet the impact of interventions for hearing loss on hearing handicap in the long term remains understudied. This article reports hearing handicap at 6 months, 12 months, and 5 years after either hearing aid provision or cochlear implantation. Study Design Observational study. Methods A study of 115 participants from the Studying Multiple Outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
3
7
0
Order By: Relevance
“…A 2017 Cochrane review of hearing aids included a study that used the full-length HHIE (score range, 0-100) and found a mean difference of –10.54 in a community-based sample with hearing aid use . In addition, the improvement in self-perceived communication function was maintained through 12 months postintervention and was comparable with findings of hearing aid users 12 months after fitting …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…A 2017 Cochrane review of hearing aids included a study that used the full-length HHIE (score range, 0-100) and found a mean difference of –10.54 in a community-based sample with hearing aid use . In addition, the improvement in self-perceived communication function was maintained through 12 months postintervention and was comparable with findings of hearing aid users 12 months after fitting …”
Section: Discussionsupporting
confidence: 79%
“…To the authors’ knowledge, this randomized clinical trial was the first of a CHW-delivered hearing care intervention designed for older adults that included provision of amplification . The improvements in self-perceived communication function were comparable in magnitude with improvements documented for older adults who received conventional clinic-based hearing care with provision of hearing aids by audiologists . Hearing aid users in one study had a comparable mean baseline score of 18.7 with an improvement in self-perceived communication function of –7.96 on the HHIE-S 6 months following receipt of hearing aids fit by audiologists in a US-based academic audiology practice .…”
Section: Discussionmentioning
confidence: 77%
“…As stated above, earlier studies with a prolonged observation period suggested that on the long run HRQoL of CI patients might decrease again (7,8,15). In our sample, however, a significant decrease of hearing-specific HRQoL could not be observed.…”
Section: Discussionmentioning
confidence: 89%
“…Finally, Kim et al (8) analyzed the 5-year effect of aural rehabilitation (through a hearing aid or a CI) on the hearing handicap of the patients. For this purpose, the authors administered to Hearing Handicap Inventory for the Elderly-Screening (HHIE-S) to 51 CI patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, CI users get more benefits than HA users. 10 BAHA has also been a good choice for aural atresia patients. And the patient with BAHA had aural atresia.…”
Section: Discussionmentioning
confidence: 99%